FAKTOR PENGARUH KEPUASAN KONSUMEN BUSANA MUSLIMAH DI ONLINE SHOP - Widyarini, Widyarini (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2015)
This research objective is to know the influence of products, prices, services and advertising on purchasing satisfaction on Moslemâs fashions on the online shop with the decision to buy as a moderating variable. The requirements to become a respondent is at least ever make a purchase on the moslemâs fashions online shop. The number of respondents as many as 127 people, taken by convenience sampling method, and the respondents fill out questionnaires via the web. The results showed that advertisement and product have a positive strong significant impact and service has a positive moderate significant impact to the decision to buy. Whereas prices and trust have no effect at all. The study also proves that the decision to buy was able to give satisfaction to the buyer.